Isu Penyatuan Akuntansi Atas Aset Tak Berwujud - Rosinta Ria Panggabean (Binus Business Review, 2013)
Globalization, technological innovation, and intense competition made companies change from laborbased business to knowledge-based business. Investors use financial statements published by the company as a basis for their investment decisions. Difficulties to compare and interpret financial statements prepared by different rules have led to demands from practitioners and academics on international harmonization, and even support for the unification of accounting standards around the world. Thus, the unification (convergence) of accounting is a big issue, especially at this time which the balance sheet of asset is increasingly dominated by intangible assets. Difficulties to recognize and to record the intangible assets in the financial statements especially Statement of Financial Position are regarded as a major issue in accounting for intangible assets. This article is a literature review of accounting for intangible assets and the impact of globalization, science, and technology against it. The discussion began with outlining the issue of unification of international accounting standards, the advantages, disadvantages, and the parties concerned in relation to accounting convergence. Article discussed later on intangible assets, along with the controversy issues that arised. Alternative solutions along with conclusions and suggestions were at the end of this article.